Legal Standing Ahli Waris Dalam Gugatan Pembagian Harta Bersama Dan Warisan: Analisis Yuridis Atas Putusan Verstek Nomor 547/Pdt.G/2024/Pn Jkt.Pst - Rayi Kharisma Rajib; Afrilia Era Vazira; Nina Handayani (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study discusses the concept of legal standing of heirs in Indonesian civil law and its application in Verstek Decision Number 547/Pdt.G/2024/PN Jkt.Pst. The main problem focuses on how the legal position of heirs is determined and its implications for legal certainty and protection of rights. The research method used is juridical-normative with a statutory approach and a case approach. The results of the study show that normatively, the legal standing of heirs is sourced from the provisions of the Civil Code, especially Articles 830, 832, and 833, which provide legal legitimacy to heirs to file a lawsuit. However, in practice, the recognition of legal standing relies heavily on formal proof. In the judgment analyzed, the lawsuit was rejected due to the lack of authentic evidence regarding the marital relationship, despite the existence of a factual family relationship. This shows that there is a tension between legal certainty and substantive justice. Therefore, a balance is needed between a formal approach and the protection of rights so that the law provides not only certainty, but also justice.